Systematic Literature Review: Irritant Contact Dermatitis Among Palm Oil Harvesters - Helga Pasadena; Yuharika Pratiwi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Irritant Contact Dermatitis (ICD) is a common occupational health issue among palm oil harvesters, who are frequently exposed to irritants such as crude palm oil, fertilizers, and pesticides. ICD is characterized by inflammation of the skin resulting from direct contact with irritants that disrupt the skin barrier without involving an allergic response (Diepgen et al., 2016). This review systematically examines global research on ICD in palm oil harvesters, focusing on its etiology, pathophysiology, prevalence, risk factors, clinical manifestations, diagnostic approaches, and management strategies.